Field-based Assessment of the Effectiveness of Rust Resistance Genes Under Field Conditions in Lebanon, Morocco and Tunisia in 2024 - Nazari, Kumarse; El Amil, Rola; Al-Jaboobi, Muamar; Maafa, Ilyass; Kemal, Seid Ahmed; SBAI, Ibtihel; Ramdhane, Nasraoui; Abdsattar, Bouslimi (International Center for Agricultural Research in the Dry Areas, 2024)
Trap nurseries comprising yellow, stem, and leaf rust resistance genes planted under natural infection in two locations in Lebanon and Morocco. Despite the availability of differential seeds, the trap nurseries were not planted in Tunisia. In Morocco, a high level of susceptibility to leaf rust was observed in several leaf rust genes, including Lr10, Lr11, Lr12, Lr13, and others across different locations, such as Allal Tazi and Marchouch. In contrast, resistance was noted in genes such as Lr2b, Lr3, Lr9, Lr19, Lr34, and others. In Lebanon, field observations indicated differences in yellow rust resistance across two locations, with various resistance genes (e.g., Yr1, Yr2+, Yr3, Yr5, Yr6+, Yr15, and others) remaining effective at Tel Amara and Kfarchakhna. In Marchouch, stem rust resistance genes like Sr21, Sr11, and Sr38 showed effectiveness, while others, including Sr5, Sr6, and Sr36, were ineffective. Details of effectiveness of Yr, Sr, and Lr genes in Morocco and Lebanon is provided.